Acute Interstitial Nephritis: A Rare and Unusual Side Effect of Omalizumab - Rocky Yang; Leila Moosavi MD; Sabitha Eppanapally MD; Ayham Aboeed MD; Augustine Munoz MD (SAGE Publishing, 2020)
Acute interstitial nephritis (AIN) is a relatively common cause of acute kidney injury with etiologies that include drug therapy, infections, and systemic diseases. Of these etiologies, drug therapy accounts for ~70% of AIN cases. Although any drug can cause AIN, there are no reported cases of AIN caused by omalizumab, a humanized monoclonal antibody that binds to and inhibits circulating immunoglobulin E. In this article, we share the first reported case of AIN following administration of omalizumab for the treatment of moderate to severe persistent asthma.